RETRACTED : Pengaruh strategi pembelajaran metakognitif preparing, doing, checking, dan assessing and following-up (PDCA) terhadap pengetahuan metakognitif dan prestasi belajar peserta didik kelas X MIPA SMAN 1 Turen pada materi larutan elektrolit dan non elektrolit - Binti Zulaihah; Parlan Parlan; Muhammad Su’aidy (Universitas Negeri Malang, 2021)
Following a rigorous, carefully concerns and considered review of the article published in Jurnal MIPA dan Pembelajarannya (Journal of Mathematics, Science, and Instruction) to article entitle